Band gap calculation of 2-D photonic crystal and its application towards thin film solar cell - Habib, Md. Ahsan; Suja, Mohammad Zahir Uddin; Bashar, Sunayna Binte; Ullah, Saeed Mahmud (Photonics Letters of Poland, 2011)
Two-dimensional (2-D) photonic crystals (PhCs) of square lattice have been investigated to find the complete photonic band gap. Band diagram calculations have been performed using the simulator "PWE band solver" of the software package optiFDTD, based on plane wave expansion method. Air holes in dielectric background with four different shapes have been considered. Parameters like filling fraction, rod/air hole orientation angle and material dielectric constant have been varied. It has been found that PhCs with square air holes have the largest gap; the gap-midgap ratio is 13.66% for GaAs (when filling fraction, f=0.680 and orientation angle ϑ = 30°). Finally, a proposal is made to improve the efficiency of thin film solar cell using this photonic crystal as back reflector. Full Text: PDF References J.D. Joannopoulos, S.G. Johnson, J. Winn, R. Meade, Photonic Crystals: Molding the Flow of Light (Princeton University Press, New Jersey 2008) L. Zeng, Y. Yi, C. Hong, J. Liu, N. Feng, X. Duan, L.C. Kimerlin, B.A. Alamariu, "Efficiency enhancement in Si solar cells by textured photonic crystal back reflector", Appl. Phys. Lett. 89, 111111 (2006)[CrossRef] P. Bermel, C. Luo, L. Zeng, L.C. Kimerling, J.D. Joannopoulos, "Improving thin-film crystalline silicon solar cell efficiencies with photonic crystals", Opt. Exp. 15 16986 (2007)[CrossRef] M. Qiu, S. He, "Large complete band gap in two-dimensional photonic crystals with elliptic air holes", Phys. Rev. B 60, 10610 (1999)[CrossRef] G. Qiua, F. Lina, Y.P. Licompelte, Complete two-dimensional bandgap of photonic crystals of a rectangular Bravais lattice (Elsevier Science, 2003) R. Wang, X.H. Wang, B.Y. Gu, G.Z. Yang, "Effects of shapes and orientations of scatterers and lattice symmetries on the photonic band gap in two-dimensional photonic crystals", J. Appl. Phys. 90, 4307 (2001)[CrossRef] J. Gee, "Optically enhanced absorption in thin silicon layers using photonic crystals", 29th IEEE Photovolt. Spec. Conf., pp. 150?153 (2002) J.I. Pankove, Optical Process in Semiconductors (Dover, New York 1971).